Penyuluhan PHBS Dalam Pencegahan Skabies Di Panti Asuhan Holei Roo Kabupaten Jayapura, Papua - Wattimena, Christy; Sasarari, Zusana A; Herman, Theresie Chindyana; Kristina, Yunita (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
Scabies is an infectious skin disease caused by the Sarcoptes scabiei mite. Scabies disease mostly affects children and the transmission can occur directly or indirectly. This community service aims to provide understanding about scabies disease in Holei Roo Orphanage. The results of the counseling activity on Clean and Healthy Living Behavior (PHBS) in the prevention of scabies at Holei Roo Orphanage gave a significant positive impact on increasing the knowledge and awareness of the residents of the orphanage about the importance of maintaining personal and environmental hygiene. Through interactive and practical education, the residents of the orphanage understand the ways to prevent scabies, such as washing hands with soap, keeping the bed clean, not sharing clothes or towels, and immediately reporting if they experience symptoms. The results of the activity show that this counseling is effective in shaping preventive behavior that can minimize the spread of scabies and support the creation of a healthy and comfortable living environment in orphanages